Implikasi Pendidikan Islam terhadap Perkembangan Pembelajaran Pendidikan Agama Islam - Abdul Adib (Departement of Mathematics Education, 2023)
The reason for this study was to find a creative learning model in the advancement of Islamic strict schooling learning materials. As a learning model that prompts the field of PAI learning in the light of Neuroscience and Quipper School. The exploratory information is obtained through writing perceptions connected with logical diary depictions and perceptions of references to investigate works, both physically and carefully which center around the subject of Islamic strict schooling. This examination is a writing study with subjective techniques. The aftereffects of this investigation discovered that the Neuroscience-and Quipper School-based model of creating PAI learning materials had the option to work with understudies (understudies and understudies) in learning PAI. Developing interest in learning and being imaginative in creating learning materials for Islamic strict training which have suggestions for the improvement of learning in the present modern transformation 5.0